African pilgrimage: ritual travel in South Africa's Christianity of Zion - Müller, Retief (Routledge, 2016)
Years after the end of Apartheid South Africa remains racially polarized and socially divided. In this context pilgrimage and travelling rituals serve to help those who often find themselves at the bottom end of the social ladder to make sense of their world. This book describes a South Africa that is made up of many different fragmented worlds.
paid
Keywords: African Independent Church; African-instituted churches; Christian pilgrims and pilgrimages; Christian pilgrims and pilgrimages South Africa; Christianisme Afrique du Sud; Christianity; Christianity South Africa; Independent churches; Independent churches South Africa; Rites and ceremonies; Rites and ceremonies South Africa; Rites et cérémonies Afrique du Sud; South Africa; Zion Christian Church (Limpopo; South Africa); Églises indépendantes Afrique du Sud